Pengaruh pengalaman kerja, etika, integritas, dan motivasi terhadap kualitas audit (Studi empiris pada auditor BPKP Provinsi Riau) - Ridho Hidayat; Andreas '; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of work experience, ethics, integrity and motivation auditors on audit quality on BPK auditors Riau Province.The population in this study were all fixed auditors totaling 118 auditor remains in office working BPK Riau Province. Researchers determined with a purposive sample/judgment sampling that is, all the auditors still numbering 118 people in Riau BPK office working on the inspection or audit in 2014. Analytical method used is multiple regression analysis to test the hypothesis. The results showed that only work experience, ethics, and integrity that has a positive effect on audit quality, while motivation negatively affect audit qualityKeywords: Quality audits, work experience, ethics, integrity, motivation auditors.